STUDI KUAT TARIK BIOPLASTIK DAN EDIBLE FILM DENGAN METODE BENDING ASTM D638-02A - Fitriyanti, Fitriyanti (SAINFIS: Jurnal Sains Fisika, 2023)
Tensile strength testing of bioplastics and edible films has been carried out in the physics laboratory, Makassar plantation industry center, with the aim of knowing the tensile strength of edible films and their strength. tensile strength of bioplastics, this test uses the ASTM D638-02a-2002 method, based on the results of the tensile strength test for edible films and the tensile strength of bioplastics, the results obtained in the Edible Film tensile strength test are 8.4648 N/mm2, while the tensile strength obtained in the sample is bioplastic is 0.9139 N/mm 2.